Pengaruh Variabel Internal Perbankan Terhadap Kinerja Bank Konvensional di Indonesia - Ali Akbar (J-MAS (Jurnal Manajemen dan Sains), 2019)
This research is to know the influence of internal variables of banking (amount of credit and operational expense than operating income (BOPO)) on the performance of conventional banks. The population in this research is the whole of conventional commercial banks in Indonesia year of 2010-2017. The sampel  is the conventional commercial banks by as much as 14 banks, with time series data. The method used is the analysis of partial least square (PLS). The results showed that internal variables of banking (amount of credit, BOPO) negative and no significant effect on performance of conventional banks (CAR, NPL, ROA, LDR) and amount of credit credit is an indicator of a dominant influence variation/change from a conventional banks performance factors (CAR, NPL, ROA and LDR).